2022
DOI: 10.1007/s11606-022-07779-9
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Clinical Trial of Population Health, Portal-Based Depression Screening: the PORTAL-Depression Study

Abstract: Background A population health approach to depression screening using patient portals may be a promising strategy to proactively engage and identify patients with depression. Objective To determine whether a population health approach to depression screening is more effective than screening during clinic appointments alone for identifying patients with depression. Design A pragmatic clinical trial at an adult outpatient internal medicine clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This final screening rate is similar to 57% achieved for a smaller sample (45 157 visits) with a medical assistant screening protocol versus 18% when physicians screened ( P < .0001) (Gorman et al, 2021). It is higher than rates found with medical assistants screening (33%) than with patient portal screening (43%) (Franco et al, 2023). Pfoh et al (2020) reached a rate of 59% after implementing a systemic depression screening program for physicians.…”
Section: Discussionmentioning
confidence: 68%
“…This final screening rate is similar to 57% achieved for a smaller sample (45 157 visits) with a medical assistant screening protocol versus 18% when physicians screened ( P < .0001) (Gorman et al, 2021). It is higher than rates found with medical assistants screening (33%) than with patient portal screening (43%) (Franco et al, 2023). Pfoh et al (2020) reached a rate of 59% after implementing a systemic depression screening program for physicians.…”
Section: Discussionmentioning
confidence: 68%
“…Data from the nationally representative Medical Expenditure Panel Survey in 2017 showed that just 50% of primary care patients ages 35 years and older were assessed for depression ( Kato et al, 2018 ). Even in a large scale pragmatic trial of self-screening through an electronic health record portal or a clinic-based desktop computer application screening rates only reached 43% and 33%, respectively ( Franco et al, 2023 ). Screening for cognitive impairment ostensibly occurs less frequently, though few studies have examined it directly ( Bradford et al, 2009 ; Chodosh et al, 2004 ; Kotagal et al, 2015 ; Sabbagh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The health system’s EHR is provided by Epic, which uses the MyChart electronic patient portal for patient communication, medical record access, prescription management, and appointment scheduling. An electronic patient portal-based system for anxiety and depression screening for use in the University of Chicago’s adult primary care clinic was under evaluation concurrent to this study [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples included screenshots of an introduction page and a common depression screening tool, the Patient Health Questionnaire-9, as they would appear in the patient portal. Samples were gathered from the portal-based screening tool being studied concurrently in the University of Chicago adult primary care clinics [ 40 , 41 ]. The interviews allowed up to 90 min for completion and usually lasted between 30 to 60 min.…”
Section: Methodsmentioning
confidence: 99%